The Economisation of Climate Change How the G20, the OECD and the IMF Address Fossil Fuel Subsidies and Climate Finance - Skovgaard, Jakob (Physical Sciences, 2021)
International economic institutions economise climate change, treating it as an economic rather than environmental issue. This book explores how three such institutions - G20, IMF, OECD - have addressed climate finance and fossil fuel subsidies, and the consequences of the economisation of climate change. Also available as Open Access.